2018
DOI: 10.15575/psy.v1i1.2120
|View full text |Cite
|
Sign up to set email alerts
|

Penanganan Perilaku Bullying Siswa Melalui Konseling Model Pengembangan Komitmen Beragama

Abstract: The glowing up bullying actor today certainly should be faced seriously by all side. School as one component in building students behavior is expected to set a sufficient medium that able to cut the bullying chain. Counseling program with the religious commitment development model is expected to deal with bullying behavior done by students in the school. This based on a number of studies suggest that the success of religious commitment development in dealing the difficulty behavior.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 0 publications
0
1
0
3
Order By: Relevance
“…Ulfiah suggested that the religious approach is a good way to handle the perpetrators of bullying. Religious approach counseling may provide services based on faith and piety as the main goal of education will not be achieved only through the teaching process, but also guidance counseling efforts are needed [23]. The low level of supervision at home, as well as the low level of supervision at school, is closely related to the development of bullying behavior among students.…”
Section: What Are the Efforts That Have Been Done By Bk Teachers To M...mentioning
confidence: 99%
“…Ulfiah suggested that the religious approach is a good way to handle the perpetrators of bullying. Religious approach counseling may provide services based on faith and piety as the main goal of education will not be achieved only through the teaching process, but also guidance counseling efforts are needed [23]. The low level of supervision at home, as well as the low level of supervision at school, is closely related to the development of bullying behavior among students.…”
Section: What Are the Efforts That Have Been Done By Bk Teachers To M...mentioning
confidence: 99%
“…Padahal sejumlah media massa menjelaskan tingginya angka kejadian perundungan di Indonesia, termasuk yang secara sengaja dipublikasikan oleh pelaku perundungan melalui media massa (Fikri, 2018). Beberapa penelitian terdahulu lebih mengeksplorasi mengenai dinamika psikologis yang terjadi pada korban perundungan dan bagaimana intervensi yang tepat sesuai dengan kasus perundungan yang terjadi (Ulfiah, 2008;Yuliati, 2013). Penelitian sebelumnya memang tidak banyak memaparkan data mengenai frekuensi atau jumlah secara detail kasus perundungan yang terjadi di beberapa wilayah di Indonesia.…”
Section: Pembahasanunclassified
“…School Bullying is aggressive behavior that is carried out repeatedly by someone or a group of students who have power, against other students who are weaker with the aim of hurting that person (Ulfiah, 2018). Academically, victims look less intelligent than people who are not victims or vice versa (Pandie & Weismann, 2016).…”
Section: Introductionmentioning
confidence: 99%